INTEGRITY AND ELECTION-WINNING IN INDONESIA: HOW TO CHALLENGE DEMOCRACY AMIDST THE OLIGARCHY? - Arlan Siddha; Lukman Munwar Fauzi (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
This article aims to understand and analyse the importance of electoral integrity and explain the dynamics of electoral democracy in Indonesia amidst the strong grip of the oligarchy that controls the government. However, electoral integrity is an important requirement so the oligarchy can be degraded and strengthen democracy. The research uses a qualitative method with data collection and analysis through a review of important and relevant literature. A thorough reading reveals that elections must be conducted fairly and free from fraud, malpractice, and administrative errors. In addition, political financing for political parties and increasing accountability for using more transparent and open funds are one of the main parts of preventing oligarchy. Finally, democracy requires broad public participation and involvement in order to oversee all processes of state administration by the government to be implemented properly.